2010
DOI: 10.1097/nor.0b013e3181c8ce23
|View full text |Cite
|
Sign up to set email alerts
|

Use of Inpatient Continuous Passive Motion Versus No CPM in Computer-Assisted Total Knee Arthroplasty

Abstract: Although the control group was found to be higher functioning preoperatively, there was no statistically significant difference in flexion, edema or drainage, function, or pain between groups through the 3-month study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
3
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 10 publications
1
28
3
17
Order By: Relevance
“…To the previously mentioned papers, which were about conventional TKA, Alkire et al [32] added a prospective randomized trial in 2010 which examined the effectiveness of the use of CPM in computer-assisted TKA: they concluded that CPM did not offer any significant benefit concerning the range of knee motion, pain, swelling, and knee function [32] . Additionally, the use of CPM was discouraged by the review of randomized controlled trials by Harvey et al [33] also in 2010, who supported that, in the patients who participated, range of knee motion, pain, swelling, quadriceps strength, length of hospital stay, and incidence of manipulation under anesthesia, did not show significant improvement after the use of CPM [33] .…”
Section: Tourniquet Use or Notmentioning
confidence: 99%
See 1 more Smart Citation
“…To the previously mentioned papers, which were about conventional TKA, Alkire et al [32] added a prospective randomized trial in 2010 which examined the effectiveness of the use of CPM in computer-assisted TKA: they concluded that CPM did not offer any significant benefit concerning the range of knee motion, pain, swelling, and knee function [32] . Additionally, the use of CPM was discouraged by the review of randomized controlled trials by Harvey et al [33] also in 2010, who supported that, in the patients who participated, range of knee motion, pain, swelling, quadriceps strength, length of hospital stay, and incidence of manipulation under anesthesia, did not show significant improvement after the use of CPM [33] .…”
Section: Tourniquet Use or Notmentioning
confidence: 99%
“…This effect is too small to clinically justify the use of CPM. Weak evidence that CPM reduces the need for manipulation under anesthesia Alkire et al [32] Prospective randomized study. CPM use or not for computer-assisted TKA No statistically significant difference in flexion, edema or drainage, function, or pain between groups 3 mo post-surgery Lensenn et al [31] Randomised controlled trial.…”
Section: No Evidence That Cpm Reduces Vte After Tkrmentioning
confidence: 99%
“…Alkire MR y col 24 . Determinar si el uso de CPM junto con el tratamiento estándar contribuye a reducir la hospitalización y mejora de pacientes sometidos a ATR.…”
Section: Medidasunclassified
“…Similarly, another recent randomised study demonstrated that there was no statistical difference in flexion and oedema in the CPM group versus the no- CPM group [38]. Another study aimed to compare mean knee flexion in patients on continuous passive motion and those without it after total knee arthroplasty (76 patients, 38 in each group: standardised physiotherapy from 1 st postoperative day and physiotherapy and one hour of continuous passive motion twice a day from 1 st postoperative day until discharge): again the conclusion was that continuous passive motion had no influence on knee range of motion after total knee arthroplasty at the time of discharge [39].…”
Section: Continuous Passive Motionmentioning
confidence: 99%
“…The use of CPM in the classic way after TKA can have a beneficial effect on knee flexion, post-surgery pain, knee oedema and hospitalisation, but it has no effect on extension recovery, wound healing or reduction of thromboembolic risk. Continuous passive motion can be considered as an adjuvant device to increase results in the short-term, but the effects of CPM on ROM are too small to justify its use, even if there is some evidence that CPM may reduce the need for subsequent manipulation under anaesthesia [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Continuous Passive Motionmentioning
confidence: 99%